Processos formativos em contextos emergentes: professoras alfabetizadoras e o ciclo de alfabetização - Rosa, Hellen de Prá da (2021)
This study was developed in the Master’s Course of the Graduation Program in Education, linked with the line of Research Training, Knowledge and Professional Development at Universidade Federal de Santa Maria (UFSM). The goal is to comprehend how emerging contexts imply the continuing education and pedagogical work by educators and literacy teachers. As main objectives we elected: acknowledge how emerging contexts are addressed in the formation process of educators and literacy teachers; identify the formative life experiences of teachers and the implications on their pedagogical work in emerging contexts; recognize the teachers’ conception about emerging contexts from the organization of pedagogical labor. In this study, we aim to respond “how the emerging contexts imply the continuing education and the pedagogical labor of educators and literacy teachers?” For the purpose of acknowledging the studies regarding this theme, we surveyed works done from 2015-2019, which allowed us to understand the bias of the productions, contributing to the investigation process. To elaborate the theoretical and methodological basis, we analysed the studies of Bauer and Gaskell (2002), Bolzan (2002, 2006, 2010, 2016, 2017), Connelly and Clandinin (1995), Fernandes (2009), Freitas (1998, 2002, 2010), Ferreiro (2002, 2011), Ferreiro and Teberosky (1999), Mortatti (2004, 2006, 2011), Imbernón (2009, 2010), Soares (2004, 2012), Vygotski (1993, 1994, 1996). The approach method was a qualitative survey, based on a sociocultural perspective, in which were performed interviews with teachers from municipal and state schools at Santa Maria/RS, who perform with literacy teaching (1º,2º,3º ano). Based on this research, it was possible to comprehend which contexts emerge in the teaching practices and how they imply the search for formative spaces and the meaning of pedagogical practices. The interpretation of the research material allowed us to identify that teachers accent the spaces of continuing education as essential, because they foster interaction, contributing for sharing as well as the act of thinking about the teaching practices and the organization of pedagogical practices focused on reading and writing. We also highlight the recurrence regarding the formation activities, which are labeled as living experiences that allow the construction of new meanings and reflections about the daily schools’ demands, putting on a different perspective the aspects which reflect the changes that weave the politics and globalised society.